Bioactivity of Fucoidan-Rich Extracts from Fucus vesiculosus against Rotavirus and Foodborne Pathogens - Dimitra Graikini; Arturo B. Soro; Saravana P. Sivagnanam; Brijesh K. Tiwari; Lourdes Sánchez (Marine Drugs, 2023)
Marine algae are sources of bioactive components with defensive properties of great value against microbial infections. This study investigated the bioactivity of extracts from brown algae Fucus vesiculosus against rotavirus, the worldwide leading cause of acute gastroenteritis in infants and young children. Moreover, one of the extracts was tested against four foodborne bacteria: Campylobacter jejuni, Escherichia coli, Salmonella Typhimurium, and Listeria monocytogenes, and the non-pathogenic: E. coli K12. In vitro tests using MA104 cells revealed that both whole algae extracts and crude fucoidan precipitates neutralized rotavirus in a dose-responsive manner. The maximum neutralization activity was observed when the rotavirus was incubated with 100 μg mL−1 of the hydrochloric acid-obtained crude fucoidan (91.8%), although crude fucoidan extracted using citric acid also demonstrated high values (89.5%) at the same concentration. Furthermore, molecular weight fractionation of extracts decreased their antirotaviral activity and high molecular weight fractions exhibited higher activity compared to those of lower molecular weight. A seaweed extract with high antirotaviral activity was also found to inhibit the growth of C. jejuni, S. Typhimurium, and L. monocytogenes at a concentration of 0.2 mg mL−1. Overall, this study expands the current knowledge regarding the antimicrobial mechanisms of action of extracts from F. vesiculosus.